2021
DOI: 10.3892/ol.2021.12911
|View full text |Cite
|
Sign up to set email alerts
|

A pancancer overview of FBN1, asprosin and its cognate receptor OR4M1 with detailed expression profiling in ovarian cancer

Abstract: Ovarian cancer affects >295,000 women worldwide and is the most lethal of gynaecological malignancies. Often diagnosed at a late stage, current research efforts seek to further the molecular understanding of its aetiopathogenesis and the development of novel biomarkers. The present study investigated the expression levels of the glucogenic hormone asprosin [encoded by fibrillin-1 (FBN1)], and its cognate receptor, olfactory receptor 4M1 (OR4M1), in ovarian cancer. A blend of in silico open access The Cancer Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Available evidence indicates that asprosin immunoreactivity is considerably raised in malignant mesothelioma, and can thus serve as its possible diagnostic marker [13]. Recently, Kerslake et al [11] reported that asprosin influences fertility and steroidogenesis in healthy ovaries and may act as a glucogenic peptide in ovarian cancer, whereas Li [18] found that FBN1 (asprosin encoded gene) may be a potential colon cancer marker. According to [4] , reduced asprosin levels may also be the cause of cancerrelated anorexia and cachexia syndrome in patients with gastric cancer, colorectal cancer, and other cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Available evidence indicates that asprosin immunoreactivity is considerably raised in malignant mesothelioma, and can thus serve as its possible diagnostic marker [13]. Recently, Kerslake et al [11] reported that asprosin influences fertility and steroidogenesis in healthy ovaries and may act as a glucogenic peptide in ovarian cancer, whereas Li [18] found that FBN1 (asprosin encoded gene) may be a potential colon cancer marker. According to [4] , reduced asprosin levels may also be the cause of cancerrelated anorexia and cachexia syndrome in patients with gastric cancer, colorectal cancer, and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…suggesting that it may play a role as a glucogenic peptide in ovarian cancer [11]. However, it remains to be established whether asprosin levels are changed in patients diagnosed with BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant difference was identified between cancer patients and non-cancer patients [Du et al, 2021]. In ovarian cancer, asprosin was found to be differentially expressed across all different histological subtypes [Kerslake et al, 2021]. Moreover, apoptosis is a natural defense system against neoplastic growth [Hanahan and Weinberg, 2011].…”
Section: Possible Role Of Asprosin In Cancer and Cellular Apoptosismentioning
confidence: 97%
“…Appropriate ethical approvals were in place for the use of these tissue samples, including using the Health Insurance Portability and Accountability Act (HIPAA) approved protocols. The protocol below is a brief summary, which is fully elaborated in Kerslake et al [12]. Primarily, the slide underwent de-paraffinization and antigen retrieval.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%